KERANGKA BERPIKIR SA’ID HAWWA DALAM MEMBANGUN TEORI UNIFIKASI TEMA AL-QUR’AN DALAM TAFSIR AL-ASAS FI AL-TAFSIR - Wiwin Ainis Rohtih (Journal Multicultural of Islamic Education, 2023)
This research aims to describe the background of Sa'id Hawwa's framework of thinking in building a theory of unification of Al-Qur'an themes in the reading of Al-Qur'an verses. This research uses a qualitative approach with descriptive analysis methods. While the primary sources used are Tafsir books and writings from Sa'id Hawwa, secondary data sources are used to sharpen the analysis related to Sa'id Hawwa's framework of thought.The results of the research show that this idea is based on several general principles, namely: [a] dividing the anatomy of the Qur'an into qism al-t{iwa>l, qism al-mi`i>n, qism al-matha>ni> , and qism al-mufas}s}al, [b] dividing the surahs of the Qur'an into several smaller units, [c] positioning al-Fatihah as an introduction to the Qur'an, [d] positioning the surah al-Baqarah as the body that explains the universality of al-Fatihah, as well as the mih}war for the surahs that follow it, and [e] positions the surahs after al-Baqarah as explanatory details of the meaning of the mih}wa>r verse and the imtida>d verse in al-Baqarah.